Mechanical, thermal & morphological properties of epoxy and epoxy/kenaf composites : effects of graphene content - Ibrahim, Nurul Shuhadah; Hassan, Azman; Mohamad, Zurina; Jawaid, Mohammad (2018)
The objective of this study is to determine the effect of graphene content on epoxy/graphene composite on the mechanical, thermal and morphological properties. The composites were prepared via compression molding. The graphene content were varied from 0.5 to 1.5 phr for epoxy/graphene composites preparation. The epoxy/graphene were investigated using mechanical test, thermogravimetric analysis (TGA) and field scanning electron microscopy (FESEM). The flexural modulus increased with increasing graphene content and reached the maximum value of 6936 MPa at 1 phr of graphene content which is 50% higher than neat epoxy. The flexural strength for epoxy/graphene was highest at 0.5 phr graphene content at 130 MPa which 8.3% higher than neat epoxy. From the TGA results, incorporation of graphene into epoxy composites increased the char residue and thermal stability of the composites at 0.5 phr graphene content. However, on further addition of graphene content up to 1.5 phr, thermal stability of the nanocomposites decreased due to the poor dispersion of graphene.